Concordance of HPV-DNA in cervical dysplasia or genital warts in women and their monogamous long-term male partners - Rob, Filip; Tachezy, Ruth; Pichlík, Tomáš; Škapa, Petr; Rob, Lukáš; Hamšíková, Eva; Šmahelová, Jana; Hercogová, Jana (Journal of medical virology, 2017)
Transmission of human papillomavirus (HPV) is a premise for development of cervical dysplasia and genital warts (GWs). This cross-sectional study assesses concordance of HPV types present in GWs or cervical dysplasia in women and genital infection of their monogamous male partners in conjunction with seroprevalence of HPV-6, -11, -16, and -18 antibodies. Blood was taken from both women and men, as well a smear of the urogenital area of men. HPV DNA detection in women was done in fixed paraffin embedded tissues under histological control. Of 143 couples who agreed to participate in the study, 68 met inclusion criteria. Type-specific concordance was observed in 32.5% (13/40) of couples in which women had genital warts and in 32.1% (9/28) of couples in which women had cervical dysplasia. In multivariate analysis only smoking in women was associated with concordance (P < 0.05). Prevalence of HPV-specific antibodies was high in male partners, but was not associated with presence of the same HPV type on their genitals. The same type-specific HPV antibodies were detected in 81.8% of men in couples with HPV-6 concordant genital warts, but only in 14.3% of men in couples with HPV-16 concordant cervical dysplasia (P < 0.01). These results suggest that type-specific HPV concordance in genital warts and cervical dysplasia lesions of women and genital infection of their male partners is common and similar. Higher seroconversion in couples with HPV-6 concordant genital warts compared with couples with HPV-16 concordant cervical dysplasia may be explained by viral load exposure.
Keywords: HPV; Humans; lidé středního věku; Female; mladý dospělý; dospělí; Molecular Epidemiology; séroepidemiologické studie; Genotype; lidé; couples; cervical dysplasia; molekulární epidemiologie; genital warts; Papillomaviridae; Adult; kondylomata akuminata; ženské pohlaví; Male; Middle Aged; Sexual Partners; dysplazie děložního hrdla; Seroepidemiologic Studies; Adolescent; DNA virů; DNA, Viral; Cross-Sectional Studies; Young Adult; protilátky virové; sexuální partneři; genotyp; Uterine Cervical Dysplasia; Antibodies, Viral; Condylomata Acuminata; concordance; mužské pohlaví; průřezové studie; mladiství